Molecular analysis of the role of Haemophilus influenzae porin P2 in host-pathogen interactions - Assafi, Mahde (2012)
Haemophilus influenzae type b (Hib) was a main cause of bacterial meningitis. Together with Neisseria meningitidis and Streptococcus pneumoniae, it occurred with comparable frequency prior to the introduction of conjugated polysaccharide vaccines against Hib. Despite the fact that the introduction of conjugated vaccines against Hib has virtually eradicated infection in many areas of the globe, this pathogen still causes many infections in developing countries and a number of cases of infection have been reported in fully vaccinated children in developed countries. Recent studies have focused on the mechanisms by which these pathogens invade the central nervous system through the blood brain barrier (BBB). One study revealed that the outer membrane protein OmpP2 of H. influenzae interacted with the 37/67-kDa non-integrin laminin receptor (LamR) of human brain microvascular endothelial cells (HBMECs). In this study, OmpP2 of H. influenzae was expressed and purified and its interactions with purified recombinant LamR (rLamR) were analysed. OmpP2, which is predicted to contain eight extracellular loops, was expressed in two parts: OmpP2Δ1-4, lacking loops 1-4, and OmpP2Δ5-8, lacking loops 5-8. The protein fragments were purified and their interaction with rLamR was investigated by ELISA. The LamR binding site of OmpP2 was found to be restricted to loops 1-4. Therefore, ompP2 derivatives encoding OmpP2 lacking loops 1, 2, 3 and 4 individually, were constructed. The OmpP2 derivatives were expressed and tested in rLamR-binding assays to determine which of these loops is required for LamR binding. Only OmpP2∆L2 showed dramatically decreased binding to rLamR. Accordingly, loop 2 of OmpP2 may play an important role in the interaction of H. influenzae with LamR. Therefore, ompP2 and ompP2ΔL2 null mutants were generated in H. influenzae strain Rd KW20 and utilized in subsequent characterization experiments to facilitate a study of the potential role of OmpP2 and its second loop in the pathogenesis of H. influenzae. The interaction of H. influenzae and its derivative mutants to LamR was investigated using a combination of molecular and immunological techniques, including ELISA, whole cell lysate pull-down assays, invasion and association assays and flow cytometry. H. influenzae cells either lacking OmpP2 or expressing OmpP2∆L2 showed significantly reduced rLamR-binding compared to the wild type. Furthermore, synthetic peptides based on the loop 2 sequence coupled to micro-beads mediated adherence of the beads to HBMECs. The amino acid sequence of OmpP2 loop 2 was found to be highly conserved in Hib isolates, but not in non-typeable H. influenzae, which rarely cause invasive disease. The potential roles of OmpP2 and Loop 2 in H. influenzae pathogenesis are discussed.